Pengaruh Intensitas Bermain dan Anonimitas pada Mobile Legends terhadap Kecenderungan Toxic Behaviour - Edo Ardo; Santi Delliana (UNIVERSITAS KALBIS, 2025)
Playing intensity and anonymity are one of the causes of the tendency for toxic behavior in MLBB game players. The presence of this study aims to find out how much influence the variables of playing intensity and also anonymity have on the tendency to behave toxic behavior. This study uses a positivistic paradigm, a quantitative approach, as well as an explanatory survey method. The research data were obtained from questionnaires that were processed using the multiple linear regression analysis test method. The results of this study state that there is an effect of playing intensity and anonymity in the Mobile Legends game on the tendency of toxic behavior. Based on the coefficient of determination test conducted, it is stated that the effect of playing intensity and anonymity in the MLBB game has a significant effect that is classified as not high, namely 32.1% on a person's tendency to act toxic behavior.